The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1159/000327657
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous and Peritonsillar Infiltration of Ketamine for Postoperative Pain after Adenotonsillectomy: A Randomized Placebo-Controlled Clinical Trial

Abstract: Objective: To evaluate the efficacy of preoperative intravenous or peritonsillar infiltration of ketamine for postoperative pain control in children following adenotonsillectomy. Patients and Methods: 78 children between 5 and 18 years of age who were scheduled for elective adenotonsillectomy were randomly assigned to four groups: group 1 (n = 19) received intravenous ketamine (0.5 mg/kg), group 2 (n = 21) intravenous normal saline, group 3 (n = 19) ketamine (0.5 mg/kg) injected through the tonsillar capsule, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
18
0
2
Order By: Relevance
“…Preoperative ketamine administration through the intravenous and peritonsillar infiltration both reduce the incidence and severity of postoperative pain as well as the need for analgesics in children undergoing tonsillectomy. However, peritonsillar infiltration was more effective in reducing the pain severity and need for analgesics [13]. In particular, despite being statistically insignificant, peritonsillar infiltration of ketamine showed a large effect size (>0.8) during the late postoperative period (6–24 hours).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Preoperative ketamine administration through the intravenous and peritonsillar infiltration both reduce the incidence and severity of postoperative pain as well as the need for analgesics in children undergoing tonsillectomy. However, peritonsillar infiltration was more effective in reducing the pain severity and need for analgesics [13]. In particular, despite being statistically insignificant, peritonsillar infiltration of ketamine showed a large effect size (>0.8) during the late postoperative period (6–24 hours).…”
Section: Discussionmentioning
confidence: 88%
“…Outcomes analyzed were postoperative pain (pain scores after leaving the operation room) [2][5], [8][23], postoperative (24 hours) analgesic requirements (either doses or percentage of patient receiving postoperative opioids or nonopioids analgesics)[2][4], [8][10], [12][14], [16], [19], [20], [22][25], time to first analgesic administration (opioid or nonopioid analgesics administered with a defined pain intensity target)[3]–[5], [8][10], [12][14], [18], [22], [23], [26], time to first oral uptake [2], [5], [13], [14], postoperative nausea and vomiting (percentage of patients or dose of antiemetics) [2], [8], [9], [12]–[18], [24], [25] and the occurrence of psycho-mimetic manifestations including nightmares [9], [10], [18], sleep pattern change (percentage of patients) [9], [10], [12], [19], hallucinations (percentage of patients) [5], [8], [18], [19], [25] or sedation (sedation scores) [4], [5], [8], [9], [11], [15], [17], [24]. These outcomes were compared with preoperative ketamine ...…”
Section: Methodsmentioning
confidence: 99%
“…13,17,20 Recently, Imai et al 13 performed a retrospective review of the medical records of 653 patients with endometrial cancer. They classified the patients based on the KCC score and found that there was no difference in survival between patients with KCC score 0 who were or were not treated with lymphadenectomy.…”
Section: Discussionmentioning
confidence: 99%
“…4 Os opiáceos desempenham um papel importante no tratamento da dor no período pós-operatório, a despeito de efeitos colaterais importantes 5 que podem afetar de modo significativo a recuperação do paciente após a cirurgia. 6 Assim, o manejo multimodal da dor no pós-operatório também pode ser útil para reduzir os efeitos secundários relacionados aos opiáceos. 7 A adição de novos medicamentos adjuvantes como os gabapentinoides a um regime analgésico multimodal, que mostrou ser eficaz na analgesia pós-operatória em diferentes procedimentos, pode ser razoável para diminuir os escores de dor no pós-operatório, o consumo total de opiáceos e os efeitos colaterais após nefrolitotomia percutânea.…”
Section: Introductionunclassified